Characterizing Cysteine Modifications in Parkinson’s-Linked Parkin and Their Influence on Dopaminergic Cell Health - Fehr, Travis (Université d'Ottawa / University of Ottawa, 2021)
Recessive mutations in PRKN, the gene coding for parkin, cause early-onset Parkinson disease (PD). Neuronal loss in parkin-deficient PD cases is restricted to specific dopamine-producing neuronal populations that have high oxidative stress. Our lab recently uncovered a role for parkin in redox biology, whereby the wild-type protein neutralizes reactive oxygen species (ROS) as well as reactive electrophilic species (RES), including dopamine itself and its metabolites. We propose that this may be an essential function that parkin confers in these vulnerable neurons. In the current work, I have further characterized parkin’s redox function by using mass spectrometry (LC-MS/MS) to analyze the redox state of parkin’s cysteines following exposure to H2O2 by differentially labelling oxidized vs. reduced cysteines; furthermore, I mapped adducts of reactive dopamine metabolites to specific cysteine residues. Using a differential labelling technique followed by LC-MS/MS analysis, we found that the redox state of parkin’s cysteines is altered when exposed to oxidative stress. There, increased oxidation of parkin correlated with both aggregation and insolubility, a phenomenon also observed in adult human brain. Furthermore, by using LC-MS/MS, I have detected adducts of oxidized dopamine metabolites at various cysteine residues on parkin; there, one specific site, the primate-specific residue C95, showed a particular vulnerability to modification by dopamine. This evidence confirmed our previous biochemical assays that had suggested parkin can be directly modified by dopamine. Expanding on previous data generated in our lab, which showed that the presence of wild-type (WT) parkin promotes the formation of melanin in vitro, I created a C95A mutation-carrying, recombinant parkin protein and observed that its ability to promote melanin formation in vitro was abolished. Similarly, we found that p.C95A parkin is not able to protect cells from dopamine-induced ROS stress as well as does WT parkin. Overall, these results suggest that parkin’s ability to neutralize ROS, to sequester reactive dopamine metabolites (RES) and to promote melanin formation, all via its cysteine oxidation, may confer protection of vulnerable dopamine-producing cells in adult human brain.
Keywords: Parkin; Dopamine; Cysteine; Redox; Parkinson disease; Mass spectrometry